2011
DOI: 10.1177/0194599811416318a279
|View full text |Cite
|
Sign up to set email alerts
|

The ADVANCE II Study: A Prospective, Randomized, Multi‐center Study to Assess the Safety and Efficacy of a Bioabsorbable Steroid‐Eluting Sinus Implant

Abstract: Objective: The United Airways Disease hypothesis suggests a link between upper and lower airways in asthmatics. However, there is a need to know more about nose and sinus related quality of life, sinonasal symptoms, and objective nasal air flow in asthmatics compared with healthy individuals.Method: One hundred asthmatics and 96 nonasthmatic controls underwent a prospective controlled survey from June 2009 to December 2010. Symptoms, quality of life, and nasal airflow were assessed on Visual Analogue Scales (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
181
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(188 citation statements)
references
References 0 publications
4
181
0
3
Order By: Relevance
“…Topical corticosteroids can be useful in improving healing but are limited by patient compliance due to the requirement for multiple applications, and effectiveness may be impacted by postoperative edema, discharge, and crusting within the sinus cavity. 1307 In order to improve postoperative healing, a wide variety of techniques have been developed and include the use of packing, stents, and spacers. Nasal packing is principally designed for postoperative hemostasis and in animal models some packing materials demonstrate improved wound healing.…”
Section: Xd6 Surgical Principles/techniques: Drug Eluting Packingmentioning
confidence: 99%
See 1 more Smart Citation
“…Topical corticosteroids can be useful in improving healing but are limited by patient compliance due to the requirement for multiple applications, and effectiveness may be impacted by postoperative edema, discharge, and crusting within the sinus cavity. 1307 In order to improve postoperative healing, a wide variety of techniques have been developed and include the use of packing, stents, and spacers. Nasal packing is principally designed for postoperative hemostasis and in animal models some packing materials demonstrate improved wound healing.…”
Section: Xd6 Surgical Principles/techniques: Drug Eluting Packingmentioning
confidence: 99%
“…There was also no significant corticosteroid systemic absorption or ocular toxicity. 1307,1317,1318 A meta-analysis combined the results from the 2 RCTs to demonstrate statistically significant reductions in the need for postoperative intervention, oral corticosteroid usage, polyposis, and adhesions. 1319 An economic evaluation also demonstrated that Propel TM is cost-effective in decreasing postoperative intervention.…”
Section: Xd6 Surgical Principles/techniques: Drug Eluting Packingmentioning
confidence: 99%
“…Multiple studies have demonstrated the feasibility, efficacy, and safety of the steroid-eluting spring implant for intraoperative use in the ethmoid cavity [22][23][24]. With respect to in-office placement, Matheny et al [25 && ] presented a case series of 20 CRS patients who underwent sinus implantation 5-7 days after total ethmoidectomy, allowing postoperative hemostasis to occur prior to its insertion.…”
Section: Drug-eluting Implantsmentioning
confidence: 99%
“…This same technology has already been shown to hold significant benefit when used in postoperative ethmoid cavities-reducing adhesions, middle turbinate lateralization, and polypoid change. 29 Studies are currently under way to evaluate the application of this same technology in maintenance of frontal sinus ostial patency after frontal sinusotomy. If successful, this type of localized drug delivery could be a powerful adjuvant in the management of frontal sinusitis.…”
Section: Future Directionsmentioning
confidence: 99%